2017
DOI: 10.1007/s10646-017-1874-4
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to a sublethal concentration of imidacloprid and the side effects on target and nontarget organs of Apis mellifera (Hymenoptera, Apidae)

Abstract: The use of insecticides has become increasingly frequent, and studies indicate that these compounds are involved in the intoxication of bees. Imidacloprid is a widely used neonicotinoid; thus, we have highlighted the importance of assessing its oral toxicity to Africanized bees and used transmission electron microscopy to investigate the sublethal effects in the brain, the target organ, and the midgut, responsible for the digestion/absorption of food. In addition, the distribution of proteins involved in impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 43 publications
5
27
1
2
Order By: Relevance
“…A similar effect was observed in honeybees exposed to imidacloprid [47]. The authors attributed this swelling to larger intercellular spaces within neurons present in exposed honeybees, likely due to damage in cell-cell contact resulting from alterations in the cytoskeleton.…”
Section: "T+s" Led To Degeneration Of Cholinergic Neuronsmentioning
confidence: 53%
“…A similar effect was observed in honeybees exposed to imidacloprid [47]. The authors attributed this swelling to larger intercellular spaces within neurons present in exposed honeybees, likely due to damage in cell-cell contact resulting from alterations in the cytoskeleton.…”
Section: "T+s" Led To Degeneration Of Cholinergic Neuronsmentioning
confidence: 53%
“…In our study, up-regulation of two genes (LOC113219 380 and LOC113219382) of Platelet activation pathway after exposure to amitraz (P <0.01), indicating that amitraz might influence the honeybees immunity. Previous study indicated that imidacloprid was involved in the intoxication of honeybees, it could compromise the viability of the midgut epithelium and affected protein digestion and absorption [40]. Comparison of transcriptome profiling between HearNPV-infected and control healthy Helicoverpa armigera larvae during an early stage post-inoculation, KEGG analysis indicated an enrichment of Volcano plot of differentially expressed genes in honeybees exposed to 9.4 mg/L of amitraz for 10 days.…”
Section: Plos Onementioning
confidence: 92%
“…A sublethal concentration of imidacloprid (Imidacloprid Pestanal – Sigma Aldrich) was added to the diet (aqueous solution of 50% sucrose) of the group exposed to the insecticide based on the LC 50 value (1.4651 ng imidacloprid µL −1 diet). An acetonic solution (15%) of imidacloprid was added to the mother solution and a dilution cascade was made so that the working solution had a final concentration proportional to a sublethal concentration 100 times lower than the LC 50 (LC 50/100 : 0.014651 ng imidacloprid µL −1 diet).…”
Section: Methodsmentioning
confidence: 99%